2018
DOI: 10.1111/ibi.12678
|View full text |Cite
|
Sign up to set email alerts
|

Predation risk and resource availability explain roost locations of Whimbrel Numenius phaeopus in a tropical mangrove delta

Abstract: Roosts are important sites for shorebirds in non‐breeding areas at night and during high tides. How the spatial configuration of food and risk of predation and disturbance influence roost site use in tropical locations remains poorly known. We analysed the locations of nocturnal roosts of Whimbrel Numenius phaeopus in mangroves of Sanquianga National Park, Colombia, with respect to variation in spatial variables related to food resources and risk of predation and disturbance. We contrasted characteristics of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
(79 reference statements)
0
10
0
Order By: Relevance
“…Notably, despite their common occurrence, inland agriculture landcover types were little used by Whimbrels at non‐breeding sites, where coastal sites with mangrove and intertidal landcover types were used in addition to nearby agricultural plots and aquaculture operations. Agricultural staging sites may provide abundant, high‐energy food resources during migration, but Whimbrels may otherwise derive different benefits (e.g., decreased predation risk and reduced disturbance) from undisturbed coastal habitats that are more important at non‐breeding locations (Johnston‐Gonzá and Abril 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, despite their common occurrence, inland agriculture landcover types were little used by Whimbrels at non‐breeding sites, where coastal sites with mangrove and intertidal landcover types were used in addition to nearby agricultural plots and aquaculture operations. Agricultural staging sites may provide abundant, high‐energy food resources during migration, but Whimbrels may otherwise derive different benefits (e.g., decreased predation risk and reduced disturbance) from undisturbed coastal habitats that are more important at non‐breeding locations (Johnston‐Gonzá and Abril 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of whimbrels harassed by dogs represents a small proportion of the birds detected (3.8%), but this is likely a major underestimation influenced by the small amount of time allocated to observation within each segment. In light of the high proportion of beaches used by dogs, as revealed by the track records, coupled with the behavior of whimbrels maintaining their foraging territories at each beach at nonbreeding areas (e.g., [ 62 ]), the proportion of birds harassed by dogs on a daily basis would be much higher than the numbers we report. In addition, whimbrel density within the study area was higher than that reported throughout sandy beaches at different areas of the Pacific Flyway [ 63 , 64 ], reaching similarly high values found at most relevant nonbreeding grounds for the species on Chiloé Island [ 64 ].…”
Section: Discussionmentioning
confidence: 57%
“…Often the choice of the roosts by birds is positively influenced by the position of the foraging sites (Watts andTurrin 2017, Johnston-González andAbril 2019). The choice of roost sites may also be influenced by factors like thermoregulation (Williams and Du Plessis 2013) and predation pressures (Townsend et al 2009, Johnston-González andAbril 2019). In some cases, the roost locations may be entirely outside their diurnal activity ranges (Jirinec et al 2016) or in a completely different habitat (Townsend et al 2009).…”
Section: Roosting Patterns Of Hornbillsmentioning
confidence: 99%
“…Therefore, understanding the patterns of roost site use is essential. The choice of roost sites may be influenced by access to food resources (Johnston-González and Abril 2019) preference for specific habitats (Zoghby et al 2016), protection from extreme weather (Peters and Otis 2007), predation pressure (Bock et al 2013, Johnston-González andAbril 2019), parasite avoidance (Rohner et al 2000), mate selection and anthropogenic disturbance (Peters and Otis 2007). The factors that influence roosting patterns may differ across sympatric species (Peters and Otis 2007).…”
Section: Introductionmentioning
confidence: 99%